PENGEMBANGAN E-MODUL PEMBELAJARAN DI KURIKULUM MERDEKA PADA MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI KELAS IV SD - Muhammad Subhan; Dian Estu Prasetyo; Aprilia Puspita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the lack of adequate teaching materials so that students have difficulty understanding the learning material, students tend to feel bored when participating in learning, and the teaching materials used are not attractive to students and students tend to have an audio-visual learning style. . For this reason, it is necessary to develop teaching materials that can help students in the learning process so that they can increase students' understanding of science learning. The aim of this research is to produce a book creator-assisted learning e-module in the independent curriculum on plant material that is the source of life on earth in grade 4 elementary school that is valid, practical and effective. This type of research is Research and Development (R&D) research using the ADDIE development model which consists of analysis, design, development, implementation and evaluation stages with test subjects namely class IV students at SD Negeri 05 Sitiung. The data collection instruments used are assessment instruments in the form of validation sheets, practicality sheets and effectiveness sheets. The results of the validation carried out by three validators obtained a final validation value of 85.56% in the very valid category, the practicality value of the teacher's response was 92.85% in the very practical category and the student response value was 84.59% in the very practical category, and the value The effectiveness obtained by students from the learning outcomes test was 85.71% in the very effective category. So it can be concluded that the Book Creator Assisted E-Module in the Independent Curriculum on Plants as the Source of Life on Earth in Grade IV Elementary School is interesting and feasible to be implemented in improving student learning outcomes in elementary schools.